ESTIMATION OF THE EQUATION OF STATE EXCHANGE ENERGY AND ENTROPY PARAMETERS OF A POLYMER SOLVENT PAIR BY INTRINSIC-VISCOSITY MEASUREMENTS - YILMAZ, F; BAYSAL, BM (JOHN WILEY & SONS LTD, 1993)
The intrinsic viscosity data of linear poly(4-chlorostyrene) in n-propylbenzene and isopropylbenzene were used to estimate the equation of state exchange energy (X12) and entropy (Q12) parameters. The quantities estimated for X12 were 6.7 and 8.1 J cm-3 and those of Q12 were -0.069 and -0.063 J cm-3 deg-1 in n-propylbenzene and isopropylbenzene, respectively. The average values of the chain unperturbed dimension constant (K0) and the characteristic ratio (C(infinity)) were found to be 0.55 x 10(-3) dl mol1/2 g-3/2 and 10.54, respectively, from the intrinsic viscosities measured at the corresponding theta-temperatures.
Keywords: POLY(4-CHLOROSTYRENE); INTRINSIC VISCOSITY; POLYMER SOLVENT INTERACTIONS; EQUATION OF STATE PARAMETERS; POLYSTYRENE SOLUTIONS; THERMODYNAMICS; Polymer Science